Efektivitas Pelaksanaan Monitoring Terhadap Portofolio Pembiayaan Segmen Mikro Pada Bank Syariah Indonesia KCP Pare Supratman - Laela, Rodena Yoman; Cahyani, Yutisa Tri (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
This phenomenon occurs in micro segment financing as a result of which the financing that has been provided to customers is not used properly. This research method uses field research using a qualitative approach. This research was conducted to analyze the effectiveness of monitoring the micro segment financing portfolio at Bank Syariah Indonesia KCP Pare Supratman. The results of this research show that the supporting factors for implementing monitoring are a stable government economy, a good system, while the inhibiting factors lie in the system, customers who are not honest about actual events. The effectiveness of monitoring implementation is effective if seen from the smooth payment of installments. The distribution of financing carried out by Bank Syariah Indonesia KCP Pare Supratman has complied with the procedure for analyzing prospective customers using five stages.